P Pengendalian Internal Persediaan Barang Dagang Pada Anugerah Swalayan Klaten - Dita Kartika Sari; Barus Umarella (JAKTABANGUN: Jurnal Akuntansi & Pembangunan, 2024)
Supermarkets are retail trading companies whose business activity is to buy goods from suppliers to resell to consumers in individual or retail quantities. Internal control of merchandise inventory is something that needs to be done to create effective inventory management so that it can help the company achieve its goals. This research focuses on analyzing the internal control of merchandise inventory at Anugerah Swalayan Klaten. This research was carried out using descriptive qualitative methods, then data was obtained from interviews with the head of the Anugerah Swalayan shop. The research results show that Anugerah Swalayan does not have written documents containing standard operating procedures, does not carry out stock taking and does not have an inventory stock card, which is important for a retail company to do, and also there are no security personel.